A Golgi-localized two-photon probe for imaging zinc ions1. Issue 60 (4th August 2015) - Singh, Hardev; Lee, Hyo Won; Heo, Cheol Ho; Byun, Ji Won; Sarkar, Avik Ranjan; Kim, Hwan Myung
<x xml:space="preserve">Abstract</x> A Golgi-localizable two-photon fluorescent probe for 3D monitoring of Zn2+ ions in live cells and rat brain tissues was reported.